HUBUNGAN POLA KONSUMSI JENIS MAKANAN YANG MENGANDUNG ZAT BESI PADA IBU MENYUSUI DENGAN KEJADIAN ANEMIA PADA BAYI 0 – 6 BULAN DI KOTA BINJAI TAHUN 2016 - Venny Vennesia Ginting; Etti Sudaryati; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Anemia is a condition when the number of red blood cells or the amount of hemoglobin (the oxygen-carrying protein) in red blood cells is below normal. Anemia is one of the problems that contributed to the increase in infant mortality. Binjai is the one city that can be said that the baby gets food intake only from a mother's breast. The purpose of this study was to determine whether there is a relationship between the consumption patterns of foods that contain iron moms breastfeeding with anemia in infants in 3 sub-district with a number of the highest maternal and infant, that is East Binjai district, North Binjai district and Binjai district. This research was an observational with cross-sectional design. Total population of infants are 1697, with a samples size of 60 people. Sampling was done by cluster sampling techniques / sampling area. The data obtained from the study is the quantity of iron consumption and energy sufficiency daily moms breastfeeding. Methods of data collection is done by using the form food recall 2x24 hour and food frequency form. The relationship between the incidence of anemia and iron sufficiency level is taken by the Chi-square test with p <0.05. The results showed the kind of food that is often consumed foods low in iron by 95% and rarely consumed foods high in iron by 5%. Likewise with energy sufficiency level that is less fulfilled by 63.3% and were met by 23.3%. The results also show that there is not a relationship between the pattern of consumption of foods containing iron with the incidence of anemia in infants (p = 0.222). Based on the research results, it is recommended that mothers in order to further improve the consumption of energy, protein and iron by utilizing sources of iron are diverse and for the health center to be more longer in outreach / information related to the incidence of anemia in infants is mainly an extension of moms breastfeeding mothers about food which should be consumed day. Keywords: infants, the incidence of anemia, iron sufficiency